2022
DOI: 10.2188/jea.je20210016
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Unit Occupancy in Japan, 2015–2018: A Nationwide Inpatient Database Study

Abstract: Background: Detailed data on intensive care unit (ICU) occupancy in Japan are lacking. Using a nationwide inpatient database in Japan, we aimed to assess ICU bed occupancy to guide critical care utilization planning. Methods: We identified all ICU patients admitted from January 1, 2015 to December 31, 2018 to ICU-equipped hospitals participating in the Japanese Diagnosis Procedure Combination inpatient database. We assessed the trends in daily occupancy by counting the total number of occupied ICU beds on a gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“… 27 Among the high-income countries, in 2017, South Korea was ranked third-lowest after Japan (7.3) in terms of the number of ICU beds per population. Ohbe, et al 28 reported that the 4-year mean ICU bed occupancy rate did not change from 2015 to 2018 in Japan. In contrast, our results revealed that the occupancy rate increased annually in South Korea.…”
Section: Discussionmentioning
confidence: 98%
“… 27 Among the high-income countries, in 2017, South Korea was ranked third-lowest after Japan (7.3) in terms of the number of ICU beds per population. Ohbe, et al 28 reported that the 4-year mean ICU bed occupancy rate did not change from 2015 to 2018 in Japan. In contrast, our results revealed that the occupancy rate increased annually in South Korea.…”
Section: Discussionmentioning
confidence: 98%
“…The database contains discharge abstracts and administrative claims data from voluntarily participating hospitals (18). In 2017, the database contained data for about 75% of all ICU beds and 70% of all HDU beds in Japan (17). This database includes the following patient-level data for all hospitalizations: demographic characteristics; diagnoses recoded with International Classification of Diseases , Tenth Revision (ICD-10) codes; daily procedures recorded using Japanese medical procedure codes; daily drug administrations; and admission and discharge status.…”
Section: Methodsmentioning
confidence: 99%
“…ICUs are the hospital units that provide the most advanced critical care, whereas high-dependency care units (HDUs) are the hospital units in which patient care levels and costs are between the levels found in the ICU and general ward (8). CCUs are the hospital units that provide critical care for patients with acute myocardial infarction using various structure and staffing models, and many hospitals in Japan currently use some beds in their ICUs and HDUs as CCU beds because Japan has no insurance reimbursement criteria that specify what qualifies as a CCU (11, 17). The current situation in Japan thus provides a unique opportunity to evaluate the structure and staffing model of CCUs by comparing patients treated in the ICU versus HDU.…”
mentioning
confidence: 99%
“…The database contains discharge abstracts and administrative claims data from voluntarily participating hospitals [ 16 ]. In 2017, the database contained data for about 75% of all ICU beds and 70% of all HDU beds in Japan [ 15 ]. This database includes the following patient-level data for all hospitalizations: demographic characteristics; diagnoses recoded with International Classification of Diseases, Tenth Revision (ICD-10) codes; daily procedures recorded using Japanese medical procedure codes; daily drug administrations; and admission and discharge status.…”
Section: Methodsmentioning
confidence: 99%
“…ICUs are the hospital units that provide the most advanced critical care, whereas high-dependency care units (HDUs) are the hospital units in which patient care levels and costs are between the levels found in the ICU and general ward [ 7 ]. CICUs are the hospital units that provide critical care for patients with cardiovascular diseases using various structure and staffing models, and many Japanese hospitals currently use some beds in their ICUs and HDUs as CICU beds for patients with acute heart failure because of the lack of insurance reimbursement criteria that specify what qualifies as a CICU [ 8 , 9 , 15 ]. Therefore, the current situation in Japan can provide a unique opportunity to assess the structure and staffing model of CICUs.…”
Section: Introductionmentioning
confidence: 99%